The Academic Turn of Child and Youth Care Practicum Coordination at MacEwan University - Pope, Christine; McGrath, Jenny; Stiller, Rebecca; Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2023)
The established agency-based approach to child and youth care (CYC) practicum coordination in post-secondary education is no longer sustainable. It has been impacted by the persistent expansion of professional programs requiring practicum placements for increasing student populations and must be rethought to address the changing needs of stakeholder service providers. This article discusses the creation of a non-administrative, academic CYC practicum coordination position at MacEwan University. The primary focus of this newly created position is to lead the transition from an all-inclusive agency-based placement model of field education to a multifaceted approach to coordination, which will include both research-focused and project-based practicum opportunities.